SENSITIVITY ANALYSIS OF REFERENCE EVAPOTRANSPIRATION UNDER DIFFERENT PROTECTED CULTIVATION STRUCTURES - Debaditya Gupta , K. N. Tiwari, Subhankar Debnath , Santosh D. T (International Journal of Modern Agriculture, 2020)
Precise estimation of reference evapotranspiration (ETo) plays an important role in crop water requirement studies whereas sensitivity analysis of climatic variables for estimation of ETo plays a key role in irrigation and water management. In the present study, ETo was estimated by using FAO56-Penman-Monteith method. Additionally, impact of climate variables in the ETo estimation was assessed by sensitivity analysis under open field condition as well as four different protected cultivation structures viz. poly house, polytunnel, shade net house, and shadow hall. Results indicate that ETo is maximum for open field condition and minimum for polyhouse. The sensitivity analysis results revealed that solar radiation is the most sensitive input variable for ETo estimated by using FAO-Penman-Monteith method wind speed is least sensitive for all structures and open field conditions